Metaphors of Ed Tech - Weller, Martin (Issues in Distance Education, 2022)
The criticisms leveled at online education during the Covid-19 pandemic revealed not only a lack of understanding about how educational technology can be deployed effectively, but a lack of imagination. In this refreshing and insightful volume, Martin Weller provides new ways of thinking about educational technology through a wide range of metaphors. By using metaphors as a mental model, Weller enables educators to move beyond pragmatic concerns into more imaginative and playful uses of technology and to critically examine the appropriate implementation and adoption of ed tech.